2008
DOI: 10.1080/15381500802006649
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Symptoms of Psychological Distress Experienced by Latinos Seeking HIV-Related Mental Health Care

Abstract: The purpose of this study was to gain a better understanding of the symptoms of psychological distress presented by Latinos living with HIV=AIDS upon their self-enrollment into publicly funded HIV-related mental healthcare. Latinos in this sample presented for care with significantly lower levels of psychological distress than the normative sample across three dimensions of the Brief Symptom Inventory (BSI): obsessive compulsivity (p < .05), interpersonal sensitivity (p < .05), and anxiety (p < .05). Symptoms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
4
1
Order By: Relevance
“…8 Furthermore, the study found that Latinos reported lower levels of anxiety, depression, and interpersonal sensitivity, as did this study; lower rates of depression and anxiety were unlike previous research that have consistently reported elevated levels of depression and anxiety among HIV-infected populations. 4,[13][14][15][16] Interestingly, these studies had not been conducted in a mental health clinic environment, which may play a role in the types of distress that are presented when individuals self-select into mental health care.…”
Section: Shacham Et Al 418contrasting
confidence: 54%
See 2 more Smart Citations
“…8 Furthermore, the study found that Latinos reported lower levels of anxiety, depression, and interpersonal sensitivity, as did this study; lower rates of depression and anxiety were unlike previous research that have consistently reported elevated levels of depression and anxiety among HIV-infected populations. 4,[13][14][15][16] Interestingly, these studies had not been conducted in a mental health clinic environment, which may play a role in the types of distress that are presented when individuals self-select into mental health care.…”
Section: Shacham Et Al 418contrasting
confidence: 54%
“…41,42,49 Research suggests that the BSI is a valid and reliable instrument for obtaining psychological health status data from adult populations, with internal consistency ranging from a low of 0.71 on the psychoticism dimension to a high of 0.85 on the depression dimension. 42,50,51 The BSI has also been used in previous studies focusing on HIV and AIDS 8,11,[43][44][45][46][47][48] and is considered a reliable measure for assessing distress in this population. 42,50,51 The normative sample, used as a comparison of levels of psychological distress among differing populations, for this study consisted of the adult psychiatric outpatient sample (n ϭ 1002).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study was conducted that measured symptoms of psychological distress reported by Hispanics seeking HIV‐related mental health services, but did not specifically measure depression. Psychological distress among Hispanics was mediated by engagement in HIV‐related mental health services (Basta et al . 2008a,b).…”
Section: Introductionmentioning
confidence: 99%
“…19 Furthermore, the prevalence is considerably higher than urban individuals living with HIV who self-reported symptoms indicative of a depression diagnosis. [20][21][22] Additional research is needed to examine the psychological distress levels among individuals living in rural areas in order to assist HIV service providers in addressing the unmet mental health needs of this population. This study was designed to increase understanding of the nature and range of psychological distress symptoms among rural individuals with HIV seeking mental health care and compare those to their urban counterparts.…”
Section: Introductionmentioning
confidence: 99%